2017
DOI: 10.1038/srep41223
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamics Regulate Fibronectin Assembly via PECAM

Abstract: Fibronectin (FN) assembly and fibrillogenesis are critically important in both development and the adult organism, but their importance in vascular functions is not fully understood. Here we identify a novel pathway by which haemodynamic forces regulate FN assembly and fibrillogenesis during vascular remodelling. Induction of disturbed shear stress in vivo and in vitro resulted in complex FN fibril assembly that was dependent on the mechanosensor PECAM. Loss of PECAM also inhibited the cell-intrinsic ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Fibronectin, a protein previously known to be enriched in CADASIL vessels and shown to increase levels in blood vessels of CADASIL patients ( 18 ), was upregulated and demonstrated clinical congruence with disease progression in the CADASIL-Early cohort. While FN1 plays a critical role in vascular remodeling after hypoxia- or hypertension-induced vessel injury ( 65, 66 ), its aggregation in tissues may be detrimental by promotion of thrombogenesis ( 67, 68 ), neuroinflammation ( 69 ), and arrest of myelination ( 70 ), all thought to be components of chronic cSVD and stroke-related VCID. Upregulated CADASIL FN1 levels were positively associated with increased cerebral atrophy and cognitive deterioration in our Early cohort, emerging as a critical, possibly neurodegenerative factor in CADASIL, which warrants exploration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin, a protein previously known to be enriched in CADASIL vessels and shown to increase levels in blood vessels of CADASIL patients ( 18 ), was upregulated and demonstrated clinical congruence with disease progression in the CADASIL-Early cohort. While FN1 plays a critical role in vascular remodeling after hypoxia- or hypertension-induced vessel injury ( 65, 66 ), its aggregation in tissues may be detrimental by promotion of thrombogenesis ( 67, 68 ), neuroinflammation ( 69 ), and arrest of myelination ( 70 ), all thought to be components of chronic cSVD and stroke-related VCID. Upregulated CADASIL FN1 levels were positively associated with increased cerebral atrophy and cognitive deterioration in our Early cohort, emerging as a critical, possibly neurodegenerative factor in CADASIL, which warrants exploration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we have described an affordable and reproducible experimental method to study the effect of cancer therapy on atherosclerotic lesion formation. In addition, atherosclerosis lesion formation at the aortic root and aortic arch areas may not be directly related to disturbed flow-induced atherogenesis, because it has been reported that fibronection expression is higher in these areas ( 35 ). By focusing on the lesions formed after PCL, we can evaluate the role of disturbed flow in cancer therapy-mediated vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…3). The Fiji image analysis software (Chen et al, 2017) and morphological analysis (Canver & Morss Clyne, 2017) were also used to analyze FN orientation. The Fiji image analysis software quantified FN alignment by implementing Fourier analysis which has limited ability to distinguish small fiber alignment changes (Palmer & Bizios, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Fourier analysis (Ng et al, 2005; Marquez, 2006), edge detection (Yoshigi et al, 2003; Vartanian et al, 2008), and fractal analysis (Fuseler et al, 2007) are commonly used to quantitatively analyze actin fiber alignment. Recently, several new studies have quantified FN alignment with edge detection (Figueroa et al, 2014), morphological analysis and (Canver & Morss Clyne, 2017) the Fiji image analysis software (Chen et al, 2017). Nevertheless, edge detection and Fiji image analysis software may not suitable for FN quantification because FN fibers displayed in fluorescence images have poorly defined borders and multiple branch points (Figueroa et al, 2014; Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation